Role of oral antibiotic preparation in bowel preparation for colorectal surgery in reducing surgical site infection - Kumari, Upasna; Ranjan, Alok; Kumar, Ajay; Thakur, Indra S. (International Journal of Research in Medical Sciences, 2023)
Background: Mechanical bowel preparation for colorectal surgeries is thought to clear the bowel lumen of stool, thus decreasing intraluminal pressure of hard, potentially impacting stool and reduce ischemia at the new anastomosis. This reduces the dreaded complication of organ space surgical site infection (SSI) that leads to anastomotic leak which is most commonly seen in colorectal surgeries. Oral antibiotic preparation is thought to reduce the bacterial concentration of colonic mucosa which is thought to further bring down the incidence of organ space SSI in colorectal surgery. Aim of this study was to evaluate the role of oral antibiotics given preoperatively as an adjunct to mechanical bowel preparation and intravenous antibiotics, in reducing SSI in colorectal surgeries. Methods: Comparative study of 60 cases of colorectal surgery divided into two equal groups (group A-patients who received oral antibiotic preparations (OABP) with mechanical bowel preparations (MBPs) and ivAb preoperatively (oral antibiotic preparation and mechanical bowel preparation +intravenous antibiotic) versus group B-patients who only received MBP and ivAb preoperatively. Outcomes of SSI results were compared. Results: Incidence of SSI in group A was 16% whereas it was 40% in group B. Incidence of anastomotic leak in group A was 3.3% and in group B was 13.3%. E. coli was found in the pus culture of 60% cases of SSI in study groups whereas S. aureus was found to be the causative organism in rest of the cases that developed SSI. Conclusions: The study supports the use of OABP as an adjunct to MBP and ivAb preoperatively in colorectal surgery for the prevention of SSI and its related complications.